A Simple Approach to Assess VT During a Field Walk Test - Dourado, V. Z.; Banov, M. C. [UNESP]; Marino, M. C.; de Souza, V. L.; Antunes, L. C. de O. [UNESP]; McBurnie, M. A. (Georg Thieme Verlag Kg, 2010)
We aimed to examine whether the ventilatory threshold (VT) during an incremental shuttle walk test (ISWT) could be determined using heart rate variability (HRV) analysis. Further aims were to assess variables capable of predicting performance in the ISWT and the intensity of this test. Beat-to-beat RR intervals and gas exchange values in 10 healthy subjects (31-83 years; 7 men) were collected during the ISWT. The ventilatory equivalent was used to assess VT from respiratory components. To determine the HRV threshold (HRVT), the instantaneous beat-to-beat variability values of the RR intervals at each stage of exercise were graphically plotted against walking speed (WS). The oxygen consumption at HRVT was calculated (VO(2)HRVT). No significant differences were found between walking speed (WS) at VT and WS at HRVT (5.04 +/- 1.00 vs. 5.10 +/- 1.04 km/h; p = 0.89). Linear regression analysis revealed a strong correlation between VO(2)VT and VO(2)HRVT (r(2) = 0.896). The Bland and Altman plot analysis revealed an agreement between VO(2)VT and VO(2)HRVT (-0.05; 95 % CI: -0.30-0.20 L/min). Thus, the VT can be assessed during the ISWT using a simple heart monitor. The ISWT may be a useful tool to assess exercise capacity and prescribe walking programs.
Keywords: heart rate variability; shuttle walk test; exercise testing